Sosialisasi Dan Penyuluhan Hukum Tentang Hibah, Wasiat, Wakaf, Dan Waris Di Wilayah Kecamatan Cinere Kota Depok - Baihaki , Ahmad; Syahyu , Yulianto; Rohman , Adi Nur; Sugiono, Harinanto (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2020)
Grants, wills, endowments, and inheritance are legal instruments that are often used by someone to transfer their assets or wealth to others. But in practice, these four things become legal issues in society, especially for Muslim residents. Legal settlement of. This case was settled by the Religious Court. Based on case data that entered the Depok City Religious Court for the past five years until 2019, there were 24 grant cases approved, 20 wills, 8 endorsed cases, and 48 s allocation for inheritance. Some of the things behind this case and the most crucial is due to the ignorance of the community against the provisions of Indonesian law regarding grants, wills, endowments, and inheritance. On that basis, a Lecturer in the Faculty of Law of the University of Bhayangkara, Greater Jakarta, conducted socialization and legal counseling on grants, wills, endowments, and inheritance on Compilation of Islamic Law for the people in the Cinere District area. The will, endowments, and inheritance in the Compilation of Islamic Law is still very minimal. After the socialization and discussion of the law, the community's knowledge and awareness will require the implementation and legalization of grants, wills, endowments, and inheritance to improve legal problems up to the increasingly increasing religious court. The output resulting from this activity is planned to be made a waqf pocketbook as an additional reference about the legal grants, wills, endowments, and inheritance according to the Compilation of Islamic Law. Besides, the results of the activities are published in the form of implementation reports and published in scientific journals to provide comprehensive and academic-wide benefits and practical levels.